PREPARATION AND CHARACTERIZATION OF SONNERATIA ALBA LEAF EXTRACT MICROCAPSULES BY SOLVENT EVAPORATION TECHNIQUE - MUHAIMIN, MUHAIMIN; LATIFAH, NOR; CHAERUNISAA, ANIS YOHANA; AMALIA, ERI; ROSTINAWATI, TINA (International Journal of Applied Pharmaceutics, 2022)
Objective: Sonneratia alba leaves were used by the community for traditional medicine to cure muscle pain, back pain, antioxidants, rheumatism, malaria, wounds, tuberculosis (TB) and as a spermicide. S. alba leaves extract was easy to damage because of the light exposure, change of pH, weather and a long period of storage time. The problem can be solved by coating the extract with a microencapsulation technique. The purpose of this research was to formulate the microcapsules of S. alba leaves extract with solvent evaporation technique using Ethocel 10 cP and Eudragit E100 as a matrix. Methods: S. alba leaves were extracted using ethanol 96%. This extract was dried by a rotary evaporator. The microencapsulation process of S. alba leaves extract was done by solvent evaporation technique (O/W: oil in water). The formula of S. alba leaves extract microcapsules was designed into six formulas (Eudragit E100: EA1, EA2, EA3 and Ethocel 10 cP: EB1, EB2, EB3). Microcapsules of S. alba leaves extract were characterized for particle size in terms of surface morphology by scanning electron microscope (SEM) and encapsulation efficiency. Antioxidant activity of the formulation have been evaluated by DPPH method. Physical characterization on microparticles was performed by conducting entrapment efficiency and SEM picture. Results: In this research, the microparticles containing S. alba extract has been developed by using ethyl cellulose (Ethocel 10 cP) and eudragit (Eudragit E100) as the polymer matrix. The results showed that a high concentration of polymer (Ethocel 10 cP and Eudragit E100) used in microencapsulation resulted in better S. alba leaves extract microcapsules in terms of physical characteristics. Particle size of microcapsules containing S. alba leaves extract were in the range of 0.701 to 1.163 μm. Encapsulation efficiency (% EE) was categorized as poor because the value were ≤ 80% to which 74.386% (EB3) and 75.248% (EA1). SEM picture of EA1 (Eudragit E100) revealed that the surface of microcapsule were rough and porous. When Ethocel 10 cP was used as a polymer, a smoother surface and less visible pores of microcapsule were obtained. The antioxidant ability of S. alba leaves extract microcapsule showed that IC50 values were 53.26 ppm. Conclusion: It can be concluded that microcapsules of S. alba leaves extract can be prepared by solvent evaporation technique using Eudragit E100 and Ethocel 10 cP as polymer. S. alba leaves has potent antioxidant activity either as an extract or after being formulated into microcapsules.